Influence of Protein Intake, Race, and Age on Responses to a Weight-Reduction Intervention in Obese Women. Issue 5 (11th April 2017) - Bales, Connie W; Porter Starr, Kathryn N; Orenduff, Melissa C; McDonald, Shelley R; Molnar, Karen; Jarman, Aubrey K; Onyenwoke, Ann; Mulder, Hillary; Payne, Martha E; Pieper, Carl F
Abstract: Background: Women have higher rates of obesity than men and develop more pronounced functional deficits as a result. Yet, little is known about how obesity reduction affects their functional status, including whether their responses differ when protein intake is enhanced. Objective: The aim of this study was to confirm the feasibility of delivery of a higher-protein (balanced at each meal) calorie-restricted diet in obese women and determine its efficacy for influencing function and retention of lean mass. Method: Obese community-dwelling women [ n = 80; body mass index (in kg/m 2 ), in means ± SDs: 37.8 ± 5.9; aged 45–78 y; 58.8% white] were enrolled in a weight-loss (−500 kcal/d) study and randomly assigned to either a Control–Weight-Loss (C-WL; 0.8 g protein/kg body weight) group or a High-Protein–Weight-Loss (HP-WL; 1.2 g protein/kg body weight; 30 g protein 3 times/d) group in a 1:2 allocation. Primary outcomes were function by 6-min walk test (6MWT) and lean mass by using the BodPod (Life Measurement, Inc.) at 0, 4, and 6 mo. Results: Both groups reduced calorie intakes and body weights ( P < 0.001), and the feasibility of the HP-WL intervention was confirmed. The 6MWT results improved ( P < 0.01) at 4 mo in the HP-WL group and at 6 mo in both groups ( P < 0.001). Both groups improved function by several other measures while slightly decreasing ( P < 0.01) lean mass (−1.0 kg, C-WL; −0.6 kg, HP-WL). Weight loss was greater in white than in black women at both 4 mo (6.0 ± 3.6 compared with 3.7 ± 3.4 kg; P < 0.02) and 6 mo (7.2 ± 4.8 compared with 4.0 ± 4.7 kg; P < 0.04) and tended to be positively related to age ( P < 0.06). Conclusions: A clinically important functional benefit of obesity reduction was confirmed in both study groups, with no significant group effect. Our findings of racial differences in response to the intervention and a potential influence of participant age lend support for further studies sufficiently powered to explore the interaction of race and age with functional responses to obesity reduction in women. This trial was registered at clinicaltrials.gov as NCT02033655.